Challenges in Perioperative management of spontaneous acute subdural hematoma in haemophilia patients (Nepal Journal of Neuroscience, 2022)
Intracranial hemorrhage in patients with hemophilia is associated with high mortality and morbidity. We report a case of 15 years old boy with haemophilia A, who presented with a spontaneous acute subdural hematoma and underwent craniotomy for clot evacuation. The patient also received Factor VIII infusions peri-operatively along with other measures, to decrease blood loss.The patient presented with signs of raised intracranial pressure and received mannitol intra-operatively and postoperatively to prevent brain edema. Hypertonic saline (3 ml/kg of 3% solution) was also given over 30 minutes for brain relaxation. Recommendations for peri-operative preparation and management of haemophilia, especially in the setting of emergency major surgery were also reviewed.